Implementation of Christian Religious Education Based on the Independent Curriculum: Implications for the Growth of Spirituality and Academic Achievement of Class X Students of SMAN 7 Bekasi - Tambunan, Daulat Marulitua; Marlina, Ita; BMB, Aleksky; Gunawan, Yuliana (LP. Ma'arif Janggan Magetan, 2024)
This study examines the implementation of Christian Religious Education based on the Independent Curriculum at SMAN 7 Bekasi, focusing on its implications on the growth of spirituality and academic achievement of grade X students. This research uses a qualitative approach through in-depth interviews with teachers and students, classroom observations, and analysis of curriculum documents. The results of the study show that the implementation of the Independent Curriculum encourages students' active involvement in spiritual activities, such as Bible reading and prayer together, while increasing learning motivation and academic achievement. In addition, the integration of practical learning that emphasizes character development and soft skills contributes to improving the quality of interactions in the classroom. These findings show that the curriculum not only functions as an academic instrument, but also as a means of strengthening students' spiritual values. The implications of this study emphasize the importance of innovative teaching strategies that combine Christian values with a freedom-based curriculum approach. The recommendations are directed at increasing teacher capacity through ongoing training and parental involvement as educational partners. Thus, the implementation of the Independent Curriculum can make a significant contribution to the growth of spirituality and academic achievement of students.